Identifying delirium in advanced dementia in the ECT‐AD clinical trial. (20th December 2022) - Lapid, Maria I.; Forester, Brent P.; Patrick, Regan E.; Fong, Tamara G.; Green, Morgan E.; Harper, David G.; Heintz, Hannah L.; Hermida, Adriana P.; McManus, Kaitlin R.; Mueller, Martina; Nykamp, Louis J.; Petrides, Georgios; et al.
Abstract: Background: Delirium and dementia are common causes of cognitive impairment in older adults and frequently co‐exist. Delirium is associated with poor clinical outcomes when comorbid with dementia. Identifying delirium superimposed on dementia (DSD) is clinically challenging given the overlap in symptoms, including inattention, cognitive impairment, and altered level of consciousness, especially in advanced stages of dementia. Recognition of delirium is also critical in ADRD (Alzheimer's Disease and Related Dementias) clinical trials for both validity and safety reasons. The ECT‐AD study is one such trial investigating the safety and efficacy of electroconvulsive therapy (ECT) for treatment‐refractory agitation and aggression in individuals with advanced ADRD. Herein we review the Confusion Assessment Method (CAM) for identifying delirium in the ECT‐AD study. Method: Inclusion criteria for ECT‐AD are hospitalized individuals diagnosed with ADRD (ages 55–89, MMSE ≤ 15) and refractory agitation/aggression, as measured by the Cohen‐Mansfield Agitation Inventory (CMAI). Procedures for detecting baseline and treatment‐emergent delirium involve a 3‐step approach conducted by raters trained in the CAM, which assesses inattention, disorganized thinking, altered levels of consciousness, and fluctuating mental status. Step 1 involves gathering information from nurse informants regarding the patient's mental status over the past 24 hours. Step 2 involves collecting observational data through informal patient interaction (e.g., brief conversation). Step 3 is an objective assessment of cognitive status using the Severe Impairment Battery – 8 Item (SIB‐8), while also making qualitative observations about delirium features (e.g., level of consciousness). The rater then codes the CAM and determines delirium status based on these 3 steps. Result: Of our 6 consented subjects, 1 experienced delirium detected by the CAM during the Randomization Phase. The subject received three positive CAMs on consecutive treatment days, citing change in mental status, inability to arouse, restlessness, psychomotor agitation, and swearing. ECT/S‐ECT was held each treatment day and the subject was withdrawn from the Randomization Phase. Conclusion: Identifying DSD is challenging due to overlapping symptoms and the fluctuating nature of delirium. The CAM may be useful in this regard by using a multi‐step approach that incorporates observations from reliable informants, direct patient interactions, and structured cognitive assessments.